2022
DOI: 10.1111/and.14511
|View full text |Cite
|
Sign up to set email alerts
|

Genistein lowers fertility with pronounced effect in males: Meta‐analyses on pre‐clinical studies

Abstract: Genistein, an isoflavonoid, is found in a plethora of plant-based foods, and has been approved for use in various therapies. A couple of studies in adult men observed a negative correlation between genistein exposure and reproductive parameters. To assess the effects of genistein exposure on reproduction and fertility in males and females, we performed quantitative meta-analyses by pooling data from published studies on animals that assessed various reproductive parameters. Pooled analysis showed significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These findings align with prior research demonstrating that estrogenic-EDCs at lower dose ranges can increase estrogen signalling, whereas higher doses induce cytotoxicity 135 , which also relates to the non-monotonic effects characteristic of several estrogenic-EDCs 136 – 141 . For example, in utero exposures to low doses of genistein are associated with DSDs such as hypospadias in mice and humans 142 145 , demonstrating that even very low doses of estrogenic-EDCs can impact development. In the context of ED, our study reiterates the importance of testing a range of doses and treatment methods of EDCs to understand their full spectrum of effects.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with prior research demonstrating that estrogenic-EDCs at lower dose ranges can increase estrogen signalling, whereas higher doses induce cytotoxicity 135 , which also relates to the non-monotonic effects characteristic of several estrogenic-EDCs 136 – 141 . For example, in utero exposures to low doses of genistein are associated with DSDs such as hypospadias in mice and humans 142 145 , demonstrating that even very low doses of estrogenic-EDCs can impact development. In the context of ED, our study reiterates the importance of testing a range of doses and treatment methods of EDCs to understand their full spectrum of effects.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have come to the controversial conclusion. Rashid Rdeng et al (Rashid et al, 2022) found that Genistein reduced male testosterone levels, reduced sperm quality, and lowered fertility. In contrast, Reed KE et al (Reed et al, 2021) found that regardless of dose and study duration, neither soy protein nor isoflavone exposure affects TT, FT, E2 or E1 levels in men.…”
Section: Discussionmentioning
confidence: 99%
“…Variety of drugs and/or compounds has been used in the manipulation of the level of testosterone. For example, genistein has been capable of reduction of level of testosterone (Rashid et al, 2022).…”
Section: It Is Possible To Test the Hypothesis By A Variety Of Studiesmentioning
confidence: 99%